Answer :

If the roots are equal then d = b2 – 4ac = 0


Here a = (a2 + b2), b = 2 (ac + bd), c = (c2 + d2)


D = b2 – 4ac = 0


b2 = 4ac


{– 2(ac + bd)}2 = 4{(a2 + b2) (c2 + d2)}


4(a2c2 + b2d2 + 2acbd) = 4(a2c2 + a2d2 + b2c2 + b2d2)


2acbd = a2d2 + b2c2


a2d2 + b2c2 – 2abcd = 0


(ad – bc)2 = 0


ad – bc = 0


ad = bc

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses